Crisis – faithful companion of women addicted to alcohol - Włodarczyk, Ewa (My University, 2022)
Crisis, defined partly similar, partly differently in social sciences, is an inherent part of everyone’s life. Having many faces, it causes many consequences (on an ad hoc basis and in the future). The analysis of the results of studies by other researchers and mine shows that crises are strongly correlated with women’s alcohol problems. They can be diagnosed on the continuum of their life: from alcohol initiation, through progressive addiction and to the process of gradual recovery. Crises in the biographies of women addicted to alcohol can be associated in two ways: with regression or progress, with a sense of lower or higher quality of life, which are confirmed by their narratives.
Keywords: crisis; alcohol addiction; women